The Effect of Working Capital and Liquidity on Profitability at PT. Nippon Indosari Corpindo, Tbk in 2009-2017 - Eni Puji Astuti; Ayu Lestari (PINISI Discretion Review, 2019)
Every company always requires working capital that will be used to finance the daily activities of the company. This study aims to determine the effect of working capital and liquidity on the profitability of PT. Nippon Indosari Corpindo Tbk, both partially and simultaneously. The research method used by the author in preparing the descriptive thesis is quantitative, which is conducting research that describes the financial condition of the company expressed in the form of numbers. The data used is secondary data from the financial statements of PT. Nippon Indosari Corpindo Tbk, for a period of 9 years from 2009 - 2017 obtained through the IDX (Indonesia Stock Exchange). The analytical method used is the classic assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. Based on the t-test partially working capital on profitability there is an effect where tcount -3,341>  ttable 2,447 and a significance value of 0.016 <0.05 and partial liquidity on profitability has no effect where tcount 1.535 <ttable 2.447 and a significance value of 0.176> 0.05 and based on the f test simultaneously working capital and liquidity affect profitability where Fcount 5.953> Ftable 5.14 with a significant value of 0.038 <0.05